Évaluer l’impact d’un changement d’échelle sur la durabilité des services d’eau : la méthode ABAFAD - Antoine Brochet; Christophe Wittner (VertigO)
The issue of sustainability of water utilities is now well identified in the literature and is the subject of specific public policies. However, very few methodologies propose to assess the impact of future challenges on the sustainability of water utilities. However, due to the sociotechnical characteristics of drinking water utilities, these stakes (renewal of the heritage, securing the water supply, etc.) appear decisive. We are formalizing here a theoretical-empirical method called "ABAFAD" which enables the evaluation of future impacts according to two hypotheses: that of a fragmentation of the administrative organization of water services, and that of a mutualization. We then seek to answer the following question: does the change in scale of management improve the prospect of sustainability of water utilities ?